Implementasi Kebijakan Adiwiyata dalam Pengelolaan Lingkungan Sekolah Menengah Atas Negeri 4 Kupang - Junindi Mandalika Manobe; I Gusti Bagus Arjana; Robertus Se (Ridwan Institute, 2021)
This study aims to explain adiwiyata school policy in the management of the school environment of SMA Negeri 4 Kupang. In this study used qualitative descriptive research method. The data analysis tecnic use Data Collection, Data Reduction, Data Display, and Conclusions Drawing/ Verifying. The results showed that adiwiyata school policy applied in the management of the environment of State High School 4 Kupang, namely the change in vision, mission and objectives that are environmentally sound, namely